2018
DOI: 10.22270/jddt.v8i6-s.2165
|View full text |Cite
|
Sign up to set email alerts
|

Prescription auditing based on World Health Organization (WHO) prescribing indicators: A case of Dilla University referral hospital

Abstract: Introduction: Rational use of drugs requires that patients receive medications appropriate to their clinical needs, in doses that meet their own individual requirements for an adequate period of time, at the lowest cost to them and their community. The issues of irrational use of medicines is global and that a global approach coordinated by WHO with more vigorous implementation of leadership and evidence based advocacy of rational use of medicine is essential Materials and Methods: Cross-sectional descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 6 publications
5
21
14
Order By: Relevance
“…This finding is comparable with findings reported from previous Ethiopian studies which reported a percentage from 0 to 1%. 12,13,15,17 One Ethiopian study, however reported a higher result, 7.3%. 16 Failure to write weight of patients may be due to inadequate availability of weighing balance to the prescribers in the study settings.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This finding is comparable with findings reported from previous Ethiopian studies which reported a percentage from 0 to 1%. 12,13,15,17 One Ethiopian study, however reported a higher result, 7.3%. 16 Failure to write weight of patients may be due to inadequate availability of weighing balance to the prescribers in the study settings.…”
Section: Discussionmentioning
confidence: 96%
“…For example, percentage of prescription papers on which date was written were 93.5%; which was relatively higher than findings from previous similar studies conducted in Ethiopia and different parts of the world which reported a percentage of 16.1 to 89.4%. [12][13][14][15][16][17] Date should be written on all prescription papers for retrieval and legal purposes. In this study, on the other hand, name of patient was mentioned in 94.7% of the prescription papers which is comparable with findings from similar studies conducted in Jimma and Harar, Ethiopia which reported 93.3% and 93.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations